On Leo Bersani: Ten Texts. (October)
Ten writers—Zahid R. Chaudhary, Anne A. Cheng, Joan Copjec, Tim Dean, David L. Eng, David Halperin, David Kurnick, D. A. Miller, Mignon Nixon, and Spyros Papapetros—celebrate the recently departed Leo Bersani.